Impact of surgery, radiation and systemic therapy on the outcomes of patients with dendritic cell and histiocytic sarcomas. Issue 16 (November 2015) - Gounder, Mrinal; Desai, Ved; Kuk, Deborah; Agaram, Narasimhan; Arcila, Maria; Durham, Benjamin; Keohan, Mary L.; Dickson, Mark A.; D'Angelo, Sandra P.; Shukla, Neerav; Moskowitz, Craig; Noy, Ariela; et al.
Abstract Background Neoplasms of histiocytic and dendritic cell origin, including follicular dendritic cell sarcoma (FDCS), histiocytic sarcoma (HS) and interdigitating dendritic cell sarcoma (IDCS), are extremely rare, and data on their natural history and treatment outcomes are sparse. We evaluated the impact of surgery, radiation and systemic therapies on overall survival (OS). Methods We conducted a retrospective chart review of patients with FDCS, IDCS and HS treated at Memorial Sloan Kettering Cancer Center between 1995 and 2014. Results We identified 31, 15 and 7 patients with FDCS, HS and IDCS, respectively. Median age was 48.7, 42.3 and 58.8 years for FDCS, HS and IDCS, respectively. Only a slight disparity in gender distribution existed for FDCS and HS; however, IDCS predominantly affected males (6:1). The most common sites of presentation were abdomen and pelvis (42%), extremities (33%) and head and neck (57%) for FDCS, HS and IDCS, respectively. At diagnosis, 74%, 40% and 86% of patients presented with localised disease in FDCS, HS and IDCS, respectively. Patients with localised disease had significantly improved OS than those with metastatic disease in FDCS (P = 0.04) and IDCS (P = 0.014) but not in HS (P = 0.95). In FDCS and HS, adjuvant or neo-adjuvant therapy was not associated with improved OS compared with observation. In IDCS, surgery alone provided a 5-year overall survival rate of 71%. Conclusions Adjuvant or neo-adjuvant treatment in FDCS and HS did not affect OS. Patients with IDCS had an excellent outcome with surgery. In the metastatic setting, chemotherapy and small molecule inhibitors may provide benefit.